PROMOTING INCLUSION OF DEAF AND HEARING IMPAIRED IN THE SCHOOL: ACTIVITY OF HEALTH EDUCATION ON HEARING AND HEARING AID IN A UNIT OF TEACHING REFERENCE TO DEAF - MACAÉ, RJ. (Fiep Bulletin - online, 2014)
Educational strategies aimed at the inclusion of children with hearing loss in the school environment should be encouraged and developed to provide the inclusion and support them in their process of interaction with all subjects from their neighborhood. The objective was to present the results and experiences of students in an educational activity aimed at inclusion of deaf and hearing-impaired child in a school from elementary school in Macaé. We performed an activity of health education on World of the Deaf, September 30, 2013, in a reference to the deaf school, the School Health Program (SHP). The team conducted a health education activity, presenting a playful manner a primer designed to promote inclusion of deaf children 06-13 years enrolled from first to sixth year. Participated in the activity 14 classes, totaling 280 elementary students. Regarding the reporting of the graduate students about their experience in the activity, it was found that "allowed the perception of reality of special children and the importance of giving more attention to this group." It was also found that the contact with the deaf and hearing impaired children and the way they interact with others "showed that they can also lead a normal life." We conclude that the educational activity reached its goal, since 90% of the students received a booklet and 60% were interested in the contents. The student experience in the proposal was of paramount importance for future professional work with special groups.
Keywords: Deafness; Hearing Loss; Social Inclusion; Health Education.